The Source of Rag5-Mediated Resistance to Soybean Aphids Is Located in the Stem - Joshi, Kumud; Baumgardner, Joshua L.; MacPhail, Madison; Acharya, Shailesh R.; Blotevogel, Elizabeth; Dayan, Franck E.; Nachappa, Punya; Nalam, Vamsi J. (Frontiers in Plant Science, 2021)
Soybean aphid (Aphis glycines), an invasive pest, continues to threaten soybean production in the U.S. A suite of management strategies, including planting aphid-resistant cultivars, have been successful in controlling soybean aphids. Several Rag genes (Resistance against Aphis glycines) have been identified, and two are currently being deployed in commercial soybean cultivars. However, the mechanisms underlying Rag-mediated resistance are yet to be identified. In this study, we sought to determine the nature of resistance conferred by the Rag5 gene using behavioral, molecular biology, physiological, and biochemical approaches. We confirmed previous findings that plants carrying the Rag5 gene were resistant to soybean aphids in whole plant assays, and this resistance was absent in detached leaf assays. Analysis of aphid feeding behaviors using the electrical penetration graph technique on whole plants and detached leaves did not reveal differences between the Rag5 plants and Williams 82, a susceptible cultivar. In reciprocal grafting experiments, aphid populations were lower in the Rag5/rag5 (Scion/Root stock) chimera, suggesting that Rag5-mediated resistance is derived from the shoots. Further evidence for the role of stems comes from poor aphid performance in detached stem plus leaf assays. Gene expression analysis revealed that biosynthesis of the isoflavone kaempferol is up-regulated in both leaves and stems in resistant Rag5 plants. Moreover, supplementing with kaempferol restored resistance in detached stems of plants carrying Rag5. Our work demonstrates for the first time that Rag5-mediated resistance against soybean aphids is likely derived from stems.